Degradation of tungsten components exposed to deuterium plasmas in JET: an investigation into component processing, mechanical behaviour and Be–W deposits - Kerr, RW (2024)
The mechanical behaviour and structural integrity of tungsten components, specifically Langmuir probes and lamellae from the JET divertor are evaluated both in their as-received state and after exposure during the ITER-like wall campaigns. The results reveal significant disparities in the as-received microstructures of these components. The lamellae exhibit fine grains suited for high-heat flux conditions, whereas the probes display larger equiaxed grains. Electrical discharge machining (EDM) induced cracks up to 50 µm and voids in both component types, raising concerns about the mechanical integrity of these surfaces.